'Which?' supplement on contraceptives. Issue 14 (8th July 1966) - Unknown
Abstract : An extensively revised edition of this special supplement has just been published by Consumers' Association. It brings test results and brand comparisons up to date, and gives more information about oral contraception and intra-uterine devices than the 1963 edition. The report is written for lay readers, but will also be particularly useful to doctors and pharmacists who may be asked for advice on contraception. The supplement costs 10/-, including postage; it is available to members of Consumers' Association and to subscribers to the Drug and Therapeutics Bulletin.